The Transfer of Power, 1942-7 : Vol.3 Reassertion of AUthority, Gandhi's Fast and the Succession to the Viceroyalty : 21 September 1942-12 June 1943 - Editor In Chief Mansergh, Nicholas (London Her Majestys stationery office, 1971)
The transfer of power, 1942-7 : constitutional relations between Britain and India / editor-in-chief Nicholas Mansergh ; assistant editor E. W. R. Lumby, 5
Include Glossary and Index
Keywords: India -- Politics and government